A rare balanced nonrobertsonian translocation involving acrocentric chromosomes: Chromosome abnormality of t(13;15)(p11.2;q22.1) - Dalvi Rupa; Koppaka Neeraja; Chavan Deepak; Mandava Swarna (Wolters Kluwer Medknow Publications, 2016)
BACKGROUND: Balanced non-robertsonian translocation (RT), involving acrocentric chromosomes, is a rare event and only a few cases are reported. Most of the RTs are balanced involving acrocentric chromosomes with the breakpoints (q10;q10). MATERIALS AND METHODS: Chromosome analysis was performed as per standard procedure - Giemsa-trypsin banding with 500 band resolution was analyzed for chromosome identification. RESULTS: In the present study, we report a rare balanced non-RTs involving chromosomes 13 and 15 with cytogenetic finding of 46, XX, t(13;15)(p11.2;q22.1). CONCLUSION: To the best of our knowledge, this is the first such report of an unusual non-RT of t(13:15) with (p11.2;q22.1) break points.